Early Detection Training Program for Acute Hepatitis in Children for the Community of Malasom Village, Sorong Regency, Southwest Papua Province. - Nurul Kartika Sari; Alva Mustamu (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2023)
ABSTRACT The enhancement of cases of acute hepatitis in children in indonesia encourages the importance of early training detection for parents. Training this gives information about signs and symptoms of acute hepatitis in children and necessary steps taken if a child is suspected of having acute hepatitis. Besides that, training also helps parents prevent transmission of acute hepatitis in children by giving information about ways to avoid the risk of getting hepatitis.The objective of devotion to the public is to increase the knowledge, attitudes, and skills of mothers and toddlers in the detection of early acute hepatitis in children. Methods devotion to a society used is training involving 35 participants consisting of parents, cadres posyandu, village heads, secretaries, employees ward, and nurse health centre, as well assisted by 6th-semester students from the D.III Midwifery, D.III Nutrition, and D.III Nursing study programs. Devotion steps cover identification problems, development of community service programs, program implementation, program evaluation, dissemination results dedication, coaching, and development capacity society.Results of dedication to the public show that team training increases participants' knowledge. The difference in the average pre-test and post-test knowledge is -27.7, and the effect size is -2.16, which is very significant. Besides that, intervention detection of early hepatitis in children also successfully increases the respondent's attitude with the difference in the mean attitude of -17.5 and an effect size of -1.00, which shows a strong influence in increasing attitude. The data also shows a significant difference between the mean psychomotor scores pre and post-with an effect size of -1.00, indicating successful intervention in increasing psychomotor participants' skills. Training conducted on research this success increases the knowledge, attitudes, and skills of psychomotor participants related detection of early hepatitis in children. However, it is recommended to do an advanced study with notice that other possible factors influence results intervene and expand the sample and research area for more representative results. Study continuation to notice aspect qualitative for obtain more understanding good about influence intervention in period longer time. Keywords: Early Detection, Child Hepatitis, Knowledge, Attitudes, Skills, Dedication To Public